Germanium nanowires-based carbon composite as anodes for lithium-ion batteries - Yan, Qingyu (2013)
Lithium-ion batteries have been actively researched in recent years due to it being one of the most promising energy storage systems. Herein, we report a novel approach where germanium nanowires (Ge NW) are grown in gold-seeded porous carbon via the solution–liquid–solid mechanism, and the corresponding improvement observed in terms of the specific capacity of this porous carbon–germanium nanowires (PC–Ge NW) composite anode. At a current density of 160 mAg−1 and voltage window of 0.001–1.5 V, a specific capacity of 789 mAhg−1 during the 50th cycle for PC–Ge NW is achieved as compared to 624 mAhg−1 during the 50th cycle for pure Ge NW. Even though the content of the Ge is only 53.5 weight percent in the PC–Ge NW composite, it yields a better stability and higher specific capacity, indicating a synergistic effect between porous carbon and Ge nanowires. There is also potential cost savings since the use of a lower amount of Ge can bring about good cycling properties.